ACUTE CORONARY SYNDROME OUTCOMES IN WOMEN BETWEEN 40-50 YEARS OLD WITH POLYCYSTIC OVARY SYNDROME FROM THE PERSPECTIVE OF THE NATIONAL INPATIENT SAMPLE 2011-2019 - Karla Inestroza, M.D; Paola Lecompte, M.D; Ivan Mijares, M.D; Ian Ergui, M.D; Rafael Hernandez, M.D; Bertrand Ebner, M.D; Rosario Colombo, M.D (Elsevier, 2023)
Therapeutic Area: ASCVD/CVD in Women Background: Polycystic Ovary Syndrome (PCOS) involves cardiometabolic abnormalities that increase women's risk of cardiovascular disease (CVD) and are thought to increase predisposition to worse outcomes. However, the independent association of PCOS with CVD and outcomes after a cardiovascular event is still unclear. Methods: The National Inpatient Sample (NIS) Database was queried from 2011-2019 for relevant ICD-9 and -10 diagnostic and procedural codes. We identified patients admitted with acute coronary syndrome (ACS) and included those of female sex between the ages of ≥ 40 and ≤50 years. We compared baseline characteristics and in-hospital outcomes of patients with and without Polycystic Ovary Syndrome. A p-value <0.05 was considered statistically significant. Results: We identified 219,290 cases of ACS in female patients between 40-50 years old, of which, n= 842 (0.4%) had a diagnosis of PCOS. Those with PCOS were younger (44.4±3.2 years vs. 46±3 years, p <0.001), more likely to be of white race (80.6% vs. 60.1%, p <0.001), have had bariatric surgery (3.6% vs. 1.5%, p <0.001), and had a higher prevalence of Metabolic Syndrome (4.2% vs. 0.5%, p <0.001), Obstructive Sleep Apnea (15.4% vs. 6.9%, p <0.001), Non-Alcoholic Fatty Liver Disease (4.2% vs. 1.1%, p <0.001), Diabetes (56.4% vs. 37.%, p <0.001), Hyperlipidemia (70% vs. 47.8%, p <0.001), Obesity (59.7% vs. 29.2%, p <0.001), Coronary Artery Disease (63.9% vs. 59.8%, p=0.004), prior Myocardial Infarction (13.7% vs. 10.3%, p=0.001), Chronic Liver Disease (3.6% vs. 2.1%, p=0.003), and Major Depressive Disorder (25.9% vs. 15%, p<0.001) compared to those without a diagnosis if PCOS.In regards to outcomes, patients with PCOS had significantly lower in-hospital all-cause mortality (2.4% vs. 4.4%, p=0.005, OR: 0.5 [0.3-0.9]) compared to those without PCOS. There was no significant difference in other in-hospital outcomes like cardiac arrest, cardiogenic shock, acute kidney injury, need for renal replacement therapy, need for intra-aortic balloon pump placement, sepsis, or arrhythmias between groups. Conclusions: We found that women between 40-50 years old with PCOS admitted for ACS have a notably increased prevalence of risk factors strongly associated with CVD. Despite this, we found significantly lower in-hospital all-cause mortality and no association with worse outcomes and complications.